If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(z + 5) + -2 = 9z Reorder the terms: 5(5 + z) + -2 = 9z (5 * 5 + z * 5) + -2 = 9z (25 + 5z) + -2 = 9z Reorder the terms: 25 + -2 + 5z = 9z Combine like terms: 25 + -2 = 23 23 + 5z = 9z Solving 23 + 5z = 9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-9z' to each side of the equation. 23 + 5z + -9z = 9z + -9z Combine like terms: 5z + -9z = -4z 23 + -4z = 9z + -9z Combine like terms: 9z + -9z = 0 23 + -4z = 0 Add '-23' to each side of the equation. 23 + -23 + -4z = 0 + -23 Combine like terms: 23 + -23 = 0 0 + -4z = 0 + -23 -4z = 0 + -23 Combine like terms: 0 + -23 = -23 -4z = -23 Divide each side by '-4'. z = 5.75 Simplifying z = 5.75
| 1=2+-h | | -4(x+1)-2x+5=31 | | -1=3y-10 | | 3(X)+3(Y)=152 | | 3=11-2c | | 18x^4-27x^3-36x^2= | | 5x-7=4x-4 | | -3(1+3)=4(s-3) | | 11x-11=13x-11 | | 8x^2+5y=100 | | 10=2+2s | | -12+c=-7 | | 7x-5=6-3x | | -7yx+8yx= | | 5+6x-2=9-.5x | | 5X-10=(X-2) | | 4=2g-14 | | a+2b=534.60 | | -2y+x=-7x-8 | | logy=(log(logx))*(logc) | | 27-3y=3(9-y) | | lny=(ln(lnx))*(lnC) | | xq-10x=100 | | (10*120)/(x-2)=80 | | lny=ln((lnX)c) | | 7y-5x=25 | | 88x+1=90x-1 | | 3(4x+5)+3x-2=-62 | | (8.92x/133.8)=(7.17/35.85) | | 5+11x=12x-2 | | 16+5(2c-1)= | | 9=R/2-3 |